1992
DOI: 10.1523/jneurosci.12-08-03272.1992
|View full text |Cite
|
Sign up to set email alerts
|

Habenula and thalamus cell transplants mediate different specific patterns of innervation in the interpeduncular nucleus

Abstract: Innervation of specific peptidergic and cholinergic compartments of the interpeduncular nucleus (IPN) was investigated using embryonic cell suspension transplants immunoreactive for substance P (SP) and ChAT. In both neonatal and adult host rats, the IPN was first denervated of its normal SP and cholinergic input from the medial habenula by bilateral lesions of the fasciculi retroflexi (FR). In adult hosts, transplants of embryonic habenular cells placed near the denervated IPN mediated a return of the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…All of the sections were counterstained with hematoxylin. Eckenrode et al, 1992;Freed et al, 1992;Pencer et al, 1992;Poltorak et al, 1992;Snyder et al, 1992;Wictorin et al, 1992;Widner et al, 1992;Suhr and Gage, 1993;Onifer et al, 1994). Specifically, we demonstrated that CNS grafts of human NT2N cells free of any contaminating non-neuronal cells acquired a mature neuronal phenotype in vivo, and that these neuron-like cells became integrated into the CNS of nude mice where > 89% of the grafts survived.…”
Section: Discussionmentioning
confidence: 51%
“…All of the sections were counterstained with hematoxylin. Eckenrode et al, 1992;Freed et al, 1992;Pencer et al, 1992;Poltorak et al, 1992;Snyder et al, 1992;Wictorin et al, 1992;Widner et al, 1992;Suhr and Gage, 1993;Onifer et al, 1994). Specifically, we demonstrated that CNS grafts of human NT2N cells free of any contaminating non-neuronal cells acquired a mature neuronal phenotype in vivo, and that these neuron-like cells became integrated into the CNS of nude mice where > 89% of the grafts survived.…”
Section: Discussionmentioning
confidence: 51%
“…Removing the habenula output by lesioning the fasciculus retroflexus in rats reduces both the amount of time that rats spend in REM sleep and the atonia associated with REM sleep 15,16 . When fetal brain tissue that includes the habenula is transplanted into these rats the normal sleep pattern and atonia are restored 15,17 . Second, the firing of habenula neurons shows circadian rhythmicity 18 , even in slice preparations 19 .…”
Section: The Habenula and Sleepmentioning
confidence: 99%
“…For example, the medial habenular neurons express high levels of MAP1B and their axons projecting to the interpendicular nucleus are highly immunostained by mAb 1B-P (Nothias et al, 1996). This pathway shows sprouting in response to partial deafferentation (Murray et al, 1979) and habenular transplants can re-innervate the interpenducluar nucleus (Eckenrode et al, 1992). Interestingly, the presence of MAP1B-P in adult CNS correlates with that of embryonic NCAM rich in polysialic acid (Le Gal la Salle et al, 1992), suggesting that in both cases the expression of these immature forms plays a role in structural remodelling in the adult.…”
Section: Regulation Of Map1b In Lesioned Adult Cnsmentioning
confidence: 99%